Complete pathological response in rectal cancer utilising novel treatment strategies for neo-adjuvant therapy: A systematic review. Issue 8 (August 2021) - Wilson, K.; Flood, M.; Narasimhan, V.; Pham, T.; Warrier, S.; Ramsay, R.; Michael, M.; Heriot, A.
Abstract: Background: Locally advanced rectal cancer is routinely treated with neo-adjuvant long course chemoradiotherapy or short course radiotherapy, followed by total mesorectal excision. Not all patients respond to this treatment and there has been an emergence of novel treatment strategies designed to improve outcomes for these patients. This systematic review aims to assess the current novel neo-adjuvant treatment strategies being utilised in the treatment of patients with rectal cancer and how these impact pathological complete response (pCR) rates. Methods: A systematic review of the literature was performed to evaluate pathological response in patients with rectal cancer receiving novel neo-adjuvant therapy. EMBASE and Medline electronic databases were searched for relevant articles. Articles published between January 2008 and February 2019 were retrieved. Included studies underwent critical appraisal and complete pathological response rates were recorded. Results: Of the initial 1074 articles identified, 217 articles fulfilled the inclusion criteria, of these 60 articles (4359 patients) were included. Neo-adjuvant therapy delivered included novel long course chemoradiation therapy, neoadjuvant chemotherapy alone, addition of a biological agent, total neo-adjuvant therapy, novel short course radiation therapy and studies utilising biomarkers to select patients for therapy. Complete pathological response rates ranged from 0 to 60%. Conclusion: A validated novel neo-adjuvant therapy that significantly increases pCR rates in patients with rectal cancer has not been identified.